Migration, local off-farm employment, and agricultural production efficiency: Evidence from China - Yang, Jin; Wang, Hui; Jin, Songqing; Chen, Kevin Z.; Riedinger, Jeffrey; Chao, Peng (International Food Policy Research Institute, 2014)
This paper studies the effect of local off-farm employment and migration on rural households’ technical efficiency of crop production using a five-year panel dataset from more than 2,000 households in five Chinese provinces. While there is not much debate about the positive contribution of migration and local off-farm employment to China’s economy, there is an increasing concern about the potential negative effects of moving labor away from agriculture on China’s future food security. This is a critical issue as maintaining self-sufficiency in grain production will be critical for China to feed its huge population in the future.